Characteristics of Cats Admitted to Czech Shelters - Voslarova, Eva; Kubesova, Katerina; Vecerek, Vladimir (Journal of applied animal welfare science, 2019)
The aim of this study was to describe the numbers and characteristics of cats entering Czech shelters. Records of sheltered cats were collected from three cat shelters situated in different regions of the Czech Republic from 2011 to 2015. A total of 2170 cat admissions were analyzed in this study. Significantly (p < .001) greater numbers of females (56%) were admitted. Most cats (60%) were admitted when they were aged younger than six months. Cats with dark coat colors prevailed (73%), cats with medium-shade colors followed (20%), and light-colored cats were the rarest (7%). The greatest numbers of cats were admitted in summer (36%), followed by autumn (33%). The fewest cats were admitted in winter (14%). Adoption was the most common outcome for admitted cats (65%), followed by unassisted death (22%) and euthanasia (11%) due to health reasons. Only 2% of cats were reclaimed from the shelters by their original caretakers. The length of stay ranged from 0 days to 1736 days with a median of 45 days. These findings may help shelter operators define optimal strategies and operational plans.
Keywords: eutanazie u zvířat; shelter; Animals; Female; Seasons; pohoda zvířat; Mortality; Age Factors; barva; Euthanasia, Animal; Animal Welfare; ženské pohlaví; kastrace; věkové faktory; Color; roční období; season; mortalita; sex; Ownership; Cats; Male; Czech Republic; Cat; age; vlastnictví; Česká republika; zvířata; mužské pohlaví; kočky; Castration